Mechanisms contributing to visceral hypersensitivity: focus on splanchnic afferent nerve signaling. Issue 12 (4th September 2015) - Deiteren, A.; De Man, J. G.; Keating, C.; Jiang, W.; De Schepper, H. U.; Pelckmans, P. A.; Francque, S. M.; De Winter, B. Y.
Abstract: Background: Visceral hypersensitivity is a main characteristic of functional bowel disorders and is mediated by both peripheral and central factors. We investigated whether enhanced splanchnic afferent signaling in vitro is associated with visceral hypersensitivity in vivo in an acute and postinflammatory rat model of colitis. Methods: Trinitrobenzene sulfonic acid (TNBS)‐colitis was monitored individually by colonoscopy to confirm colitis and follow convalescence and endoscopic healing in each rat. Experiments were performed in controls, rats with acute colitis and in postcolitis rats. Colonic afferent mechanosensitivity was assessed in vivo by quantifying visceromotor responses (VMRs), and by making extracellular afferent recordings from splanchnic nerve bundles in vitro . Multiunit afferent activity was classified into single units identified as low threshold (LT), wide dynamic range (WDR), high threshold (HT), and mechanically insensitive afferents (MIA). Key Results: During acute TNBS‐colitis, VMRs were significantly increased and splanchnic nerve recordings showed proportionally less MIA and increased WDR and HT afferents. Acute colitis gave rise to an enhanced spontaneous activity of both LT and MIA and augmented afferent mechanosensitivity in LT, WDR and HT afferents. Postcolitis, VMRs remained significantly increased, whereas splanchnic nerve recordings showed that the proportion of LT, WDR, HT and MIA had normalized to control values. However, LT and MIA continued to show increased spontaneous activity and WDR and HT remained sensitized to colorectal distension. Conclusions & Inferences: Visceral hypersensitivity in vivo is associated with sensitized splanchnic afferent responses both during acute colitis and in the postinflammatory phase. However, splanchnic afferent subpopulations are affected differentially at both time points. Abstract : The role of splanchnic afferent nerves in visceral hypersensitivity remains unclear. Visceral sensitivity during acute TNBS‐colitis and in the postinflammatory phase was assessed in vitro by recording splanchnic afferent nerve discharge and in vivo by recording visceromotor responses to colorectal distension. Sensitization of splanchnic afferents in vitro is associated with visceral hypersensitivity in vivo both during acute colitis and in the postinflammatory phase but the different subpopulations of afferent nerves are differentially affected in the acute vs the postinflammatory phase of colitis.